2019
DOI: 10.31389/jied.28
|View full text |Cite
|
Sign up to set email alerts
|

(Il)licit Economies in Brazil: An Ethnographic Perspective

Abstract: Illicit economies are an issue of paramount importance and an opportunity for social mobility for millions in Brazil. The literature about them lacks empirical accuracy and less normative interpretive keys. Based on field research conducted between 2005 and 2018, this paper explores two stories: i) that of a young man working for illegal markets in the outskirts of São Paulo; and ii) that of a Toyota Hilux he stole. It adopts an approach centered on a theory of everyday action and focused on the boundary betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…São Paulo also hosts Brazil's most lucrative and globalized criminal enterprises and is the birthplace of Brazil's most powerful criminal faction, the First Command of the Capital (PCC). There is already a consolidated bibliography on the political importance of this criminal group in the regulation of order in the peripheries and prisons across the state of São Paulo (Biondi, 2016;Feltran, 2018Feltran, , 2019Feltran, , 2020Willis, 2015).…”
Section: Methodology and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…São Paulo also hosts Brazil's most lucrative and globalized criminal enterprises and is the birthplace of Brazil's most powerful criminal faction, the First Command of the Capital (PCC). There is already a consolidated bibliography on the political importance of this criminal group in the regulation of order in the peripheries and prisons across the state of São Paulo (Biondi, 2016;Feltran, 2018Feltran, , 2019Feltran, , 2020Willis, 2015).…”
Section: Methodology and Contextmentioning
confidence: 99%
“…However, the criminal world is also unevenly stratified, with low-level criminal actors earning relatively low incomes. Recent research has shown that illegalisms are interconnected with the formal and licit economies, and, contrary to what one might think, do not harm their 'development' or 'progress' (see, especially, Feltran, 2019). According to Feltran, cash economies allow 'dirty money' to circulate between the illegal and legal economies.…”
Section: Methodology and Contextmentioning
confidence: 99%
“…As fronteiras entre o "legal" e o "ilegal", entre o "formal" e o "informal", são porosas (Telles, 2010), e se produzem em meio a jogos de poder (Foucault, 2016). Da mesma forma, em ruptura com uma narrativa hegemônica sobre o tema, não tomamos os ditos "mercados ilegais" como espécie de "economia paralela", mas sim como parte constitutiva da economia global (Beckert e Dewey, 2017 ;Feltran, 2019). Nessa perspectiva, a produção de clivagens entre o "legal" e o "ilegal", através de discursos morais ou da implementação de leis, pode ser compreendida como estratégia de disputa pela regulação de recursos movimentados por economias informalizadas.…”
Section: Digitalização E Formalização: O Caso De Um Desmanche De Veíc...unclassified
“…The point is that neoliberal globalization is not confined to legal trade and markets (cf. Comaroff and Comaroff 2006; Galemba 2008; Nordstrom 2007) but involves translocal networks in which the legal and the illegal are entangled in complex ways (Telles 2010; Feltran 2019). Not for nothing, Misse (2018) has proposed the term “political merchandise” for goods that circulate in the interstices of the legal and the illegal in Rio de Janeiro.…”
Section: Analysis and Conclusionmentioning
confidence: 99%